Gamified Digital Worksheets with AI Feedback Support for Active Learning in Elementary Civic Education - Yustiana, Sari; Afandi, Muhamad (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to develop and test the feasibility of gamified digital worksheets with AI feedback support to promote active learning in elementary Civic Education (PKn). Method: The study employed a research and development design using the 4D model consisting of define, design, develop, and disseminate stages. The participants were fourth-grade elementary students, and the evaluation involved expert validation, a limited trial, and a broader trial. Two expert raters validated the draft across six aspects: civic education content, digital media, gamification, active learning, AI feedback support, and language. Content validity was analyzed using Aiken's V, while inter-rater reliability was calculated using percentage agreement, Cohen's kappa, and the intraclass correlation coefficient (ICC). Teacher and student responses were converted into percentages and categorized as Very Good, Good, Fair, or Poor. Results: The average Aiken's V was 0.90, with a range of 0.67-1.00, indicating that the product was highly valid. Inter-rater reliability showed 83.33% exact agreement, Cohen's kappa of 0.61, and ICC of 0.61. Teacher responses increased from 93.33% in the limited trial to 100.00% in the broader trial, while student responses increased from 97.46% to 99.15%. Novelty: The study offers a gamified worksheet model in which AI serves as a feedback and reflection support tool, while gamification and active learning remain the main pedagogical structure for strengthening civic understanding, participation, and responsibility in elementary learning.